2022
DOI: 10.3390/agronomy12040899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multi-Species Microbial Inoculants on Early Wheat Growth and Litterbag Microbial Activity

Abstract: The use of microbial consortia (MC) with complementing features is considered to be a promising method of sustainable crop intensification, potentially trumping the limited performance of single-strain applications. We assessed the effect of two novel MC on early wheat growth and litterbag microbial activity in heated and unheated soil. Pot experiments were carried out in duplicate in a greenhouse over 63 days using a completely randomized design with six replications. A range of parameters of plant growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…The high cargo capacity of char was utilized and demonstrated in this work. The microbial consortia chosen for the experiments were the MC-B and MC-C [ 40 , 41 ], previously tested on wheat T. aestivum [ 41 ] but not on wheat T. durum nor Z. mays . First, it was evaluated whether the microbes could colonize the char surface and functionalize it and the extent to which this was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…The high cargo capacity of char was utilized and demonstrated in this work. The microbial consortia chosen for the experiments were the MC-B and MC-C [ 40 , 41 ], previously tested on wheat T. aestivum [ 41 ] but not on wheat T. durum nor Z. mays . First, it was evaluated whether the microbes could colonize the char surface and functionalize it and the extent to which this was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Missing effects of PGPM application may also be due to a masking effect resulting from high nutrient availability either in pots ( Hett et al., 2022 ) or in the field ( Hett et al. 2023 ) and limited impact of stress factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, a wide range of other physiological mechanisms may affect crop growth as well. According to Hett et al. (2022) , the potential functions of PGPM include (i) the facilitated acquisition of water and nutrients (primarily N, P, and Fe); (ii) the modulation of phytohormonal balances by changing the levels of auxins, cytokinins, gibberellins, abscisic, jasmonic and salicylic acids, mediating, inter alia, stimulation of root growth and modifications of plant development; (iii) the release of volatile organic compounds and siderophores with functions in stress priming and nutrient mobilization and (iv) the reinforcement of resistance against abiotic stress factors ( Vessey, 2003 ; Martínez-Viveros et al., 2010 ; Glick, 2012 ; Glick, 2014 ; Vejan et al., 2016 and Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and formulation of multispecies bio-inputs might be advantageous over first-generation bio-inputs (single-strain), because: (1) microorganisms most probably act in a cooperative manner by providing nutrients, removing inhibitory products, and stimulating beneficial physiological traits; (2) such a diverse array of organisms might improve adaptation to a wide range of environmental conditions; (3) provision of more than one PGPB with equal or different modes of action might improve the ability of a bacterial community to promote plant growth [ 9 ]. In this way, several PGPB co-inoculation studies with promising results have been reported in crops such as soybean, maize, potato and wheat, among others [ 11 , 12 , 13 , 14 , 15 , 16 ]; however, there are few reports regarding the use of such tools on studies on horticultural crops [ 9 , 17 , 18 ]. Also, despite the enormous potential of microorganisms to promote plant growth either alone or in a mixture, the reproducibility of their beneficial effects in the field varied too much, which is frequently related to a failure of the inoculated microorganisms to colonize and establish within new environments [ 4 , 16 ].…”
Section: Introductionmentioning
confidence: 99%